PHOTOSYNTHETIC RESPONSES IN PHAEOCYSTIS ANTARCTICA TOWARDS VARYING LIGHT AND IRON CONDITIONS - Van Leeuwe M.A.; Stefels J. (My University, 2007)
The effects of iron limitation on photoacclimation to a dynamic light regime were studied in Phaeocystis antarctica. Batch cultures were grown under a sinusoidal light regime, mimicking vertical mixing, under both iron-sufficient and -limiting conditions. Iron-replete cells responded to changes in light intensity by rapid xanthophyll cycling. Maximum irradiance coincided with maximum ratios of diatoxanthin/diadinoxanthin (dt/dd). The maximum quantum yield of photosynthesis (F v /F m ) was negatively related to both irradiance and dt/dd. Full recovery of F v /F m by the end of the light period suggested successful photoacclimation. Iron-limited cells displayed characteristics of high light acclimation. The ratio of xanthophyll pigments to chlorophyll a was three times higher compared to iron-replete cells. Down-regulation of photosynthetic activity was moderated. It is argued that under iron limitation cells maintain a permanent state of high energy quenching to avoid photoinhibition during exposure to high irradiance. Iron-limited cells could maintain a high growth potential due to an increased absorption capacity as recorded by in vivo absorption, which balanced a decrease in F v /F m . The increase in the chlorophyll a-specific absorption cross section was related to an increase in carotenoid pigments and a reduction in the package effect. These experiments show that P. antarctica can acclimate successfully to conditions as they prevail in the Antarctic ocean, which may explain the success of this species.
Keywords: FLUORESCENCE; IRON; LIGHT; PHAEOCYSTIS; PIGMENTS; XANTHOPHYLL CYCLING